A First Report of Fossil Fern-like Pteropsida from Costa Rica - Gómez P., Luis Diego (1968)
Fossil fern-like Pteropsida are reported, apparently as the first record for the country, from Middle or Upper Tertiary deposits of the central-southwestern region of Costa Rica. The specimens are described as resembling the pecopteris and Mixoneura types of the Palaeozoic and some contemporary species of Thelypteris.